Ovid, Tristia 1.2 and elegy transformed - Franklinos, TE (Cambridge University Press, 2024)
This article discusses Ovid’s allusive engagement in Tristia 1.2.75–80 with his own earlier works, as well as with the works of his elegiac predecessors – Propertius and Tibullus – and of Catullus. It is argued that this suggestive intertextuality may point toward Ovid’s rearticulation of his conceptualization of elegy as it is now to be written from exile.